Constructing Narrative Identities in the Holocaust Memories/Memoirs of Three Women - Louise O. Vasvári (Hungarian Cultural Studies, 2020)
Although only a decade in age separates each one from the next, the women whose life stories are discussed here represent three distinct Holocaust generations of Hungarian-speaking women. I aim to examine the recently published memories/memoirs of these three women whose narratives are all centered in the Holocaust when the deportations began in Hungary in 1944. Their personal stories are placed within a larger socio-historical context, but treat matters which come within the personal knowledge of the writer and therefore offer precisely the kind of alternative micro-history often provided by women’s narratives. All three authors also have in common that they left their homeland as young adults and hence their stories arguably belong more broadly to the most important subgenre of life writing today. While such writing is produced by both genders, writing by females predominates. My aim is, in part, to examine in the texts under discussion the three autobiographers as self-historians in their retrospective and crafted stories told (and retold) in different contexts, so that their life stories are not merely a recapitulation of past events but rather their creation of personal narrative identities.